(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
If the role of cinema was central in the popular press over the years following the Second World War, equally crucial was the connection between stardom and sexuality which emerged and grew in this context. Among the different images appearing on the magazine «Oggi» and widely circulated between the late 1940s and the first half of the 1950s, those illustrating ‘rites of passage’ were food for thoughts for the debate about sexuality. Marriage became the main instrument for social control, while motherhood took on the function of controlling sexual desire to channel it into the regulated forms of family and procreation. The maternity of some actresses of the immediate post-war period in particular (such as Ingrid Bergman, Rita Hayworth, and Silvana Mangano) was the opportunity for celebrity’s private life to become a public tale and a regulating program on social behavior at a national level. The management and control of female body was central in the debate about community or political trends; the issue became a ‘cultural text’ with an impact on the symbols of the society of the time, which was strongly influenced by Catholic culture. By analyzing how stars were represented on popular press it is therefore possible not only to read the morality of the time, but also to bring to light the symptoms of wider social and political transformations, which find in sexuality a terrain of encounter and privileged confrontation.